2020
DOI: 10.1002/anie.201916530
|View full text |Cite
|
Sign up to set email alerts
|

Distal Allylic/Benzylic C−H Functionalization of Silyl Ethers Using Donor/Acceptor Rhodium(II) Carbenes

Abstract: Regio-and stereoselective distal allylic/benzylic C À

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…We have recently reported that 1,1,1,3,3,3-hexafluoroisopropanol (HFIP) has beneficial effects on certain rhodium-catalysed carbene reactions. 35 Therefore, we decided to explore its effect on the optimized cyclopropanation, and we were pleased to observe that 10 equiv. of HFIP could be used in place of the 10 weight equiv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported that 1,1,1,3,3,3-hexafluoroisopropanol (HFIP) has beneficial effects on certain rhodium-catalysed carbene reactions. 35 Therefore, we decided to explore its effect on the optimized cyclopropanation, and we were pleased to observe that 10 equiv. of HFIP could be used in place of the 10 weight equiv.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the poor performance of the established catalysts, newer catalysts were evaluated in the reaction. Rh 2 (S-TPPTTL) 4 (7), a recently developed catalyst with a unique selectivity prole, 27,35 emerged as the optimal catalyst for this system, giving 37 in 88% yield and 60% ee (Table 2). Optimization of the Rh 2 (R-TPPTTL) 4 ( 7)-catalysed reaction by changing solvent (entries 4-6) or changing from the methyl ester to trichloroethyl ester (entry 7), did not improve the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported that hexafluoroisopropanol (HFIP) has beneficial effects on certain rhodium-catalyzed carbene reactions. [16] Therefore, we Table 1. Scope of vinyl heterocycles aryl-diazoacetates and heteroaryl-diazoacetates compatible with previously established high-TON cyclopropanation methodology in the presence of Rh2(R-p-Ph-TPCP)4.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the poor performance of the established catalysts, a catalyst screen of several of the newer catalysts was conducted (see supplementary information for details). Rh2(R-TPPTTL)4, a recently developed catalyst with a unique selectivity profile, [11,16] emerged as the optimal catalyst for this system, giving 37 in 88% yield and 66% ee (Table 2). Interestingly, reactions of para or meta substituted aryldiazoacetates give the opposite absolute configuration to the products obtained from reactions with orthosubstituted aryldiazoacetates as determined by X-ray crystallography.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation